2004
DOI: 10.1128/cdli.11.3.627-630.2004
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Related Cytokine Patterns in Sera of Schistosomiasis Patients with Symmers' Fibrosis

Abstract: Cytokine levels were compared between schistosomiasis patients affected by intense fibrosis defined by ultrasound examination and graded from F-0 to F-3. The concentrations of interleukin-1␤ (IL-1␤), IL-4, IL-5, IL-10, IL-13, gamma interferon, and tumor necrosis factor alpha (TNF-␣) were determined by enzyme-linked immunosorbent assay of serum samples. Levels of IL-4, IL-5, and TNF-␣ in the sera of F-3 patients were significantly higher than those found in F-0 individuals, while levels of IL-13 were lower. Lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1
3

Year Published

2005
2005
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 33 publications
2
14
1
3
Order By: Relevance
“…In a recent study [53], the authors showed no significant difference in levels of IL-10 in individuals with different degrees of periportal fibrosis due to schistosomiasis. This is in agreement with Silva-Teixeira et al [25], who demonstrated no association between levels of IL-10 and parasite burden and that this cytokine may thus not be involved in periportal fibrosis development during schistosomiasis. In several studies on schistosomiasis, IL-10 appears to be a key cytokine in the regulatory process which prevents pathology.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…In a recent study [53], the authors showed no significant difference in levels of IL-10 in individuals with different degrees of periportal fibrosis due to schistosomiasis. This is in agreement with Silva-Teixeira et al [25], who demonstrated no association between levels of IL-10 and parasite burden and that this cytokine may thus not be involved in periportal fibrosis development during schistosomiasis. In several studies on schistosomiasis, IL-10 appears to be a key cytokine in the regulatory process which prevents pathology.…”
Section: Discussionsupporting
confidence: 82%
“…Reiman et al [24] discussed the involvement of IL-5 in granuloma formation around S. mansoni eggs in the liver, since this cytokine participates in eosinophil growths and activation, contributing to a significant source of profibrotic mediators such as IL-13. In addition, Silva-Teixeira et al [25] reported that serum levels of IL-5 were higher in patients with a severe degree of periportal fibrosis than in those without fibrosis. While levels of IL-5 were similar in the groups in our study, we found higher levels of IL-13 in the CSF and serum in the SMR group compared to in patients with HAM and OND.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…40 Furthermore, TNF-␣ overexpression is associated with PH, 41 although TNF-␣ blockade may not suppress experimental PH. 42 Measurement of TNF-␣ in whole lung lysates in S. mansoni infected and uninfected wild-type, IL-13R␣1 Ϫ/Ϫ , and IL-13R␣2 Ϫ/Ϫ mice revealed an increased level in only the wild-type infected mice compared with all other groups (Supplemental Figure 8C, see http://ajp.amjpathol.org).…”
Section: Org)mentioning
confidence: 99%
“…3,4 Upstream of the TH2 pathway, IL-10 is implicated in negotiating the balance between TH1 and TH2 immunity, involving a third class of T reg cells. 5,6 During chronic schistosomiasis infection, IL-10 production also reduces collateral tissue damage and TH2-induced fibrosis in the liver [7][8][9][10] in response to deposition of S. mansoni eggs. 4 In addition to have a function in host defense against helminthic infection, the TH2 pathway is pathologically activated in atopic diseases (including asthma) in response to stimulus by environmental allergens.…”
Section: Introductionmentioning
confidence: 99%